Achieving competitiveness with marketing 5.0 in new business conditions - Mihalj Bakator; Marija Vukoja; Dino Manestar (UTMS Journal of Economics, 2023)
This paper investigates the changing business paradigm, enterprise competitiveness, and the arrival of Marketing 5.0. To remain competitive, businesses must adapt to digital marketing, innovative technology, and a growing emphasis on ethical considerations. The paper delves into the factors that influence competitiveness, including the external environment, internal capabilities, strategic choices, and ethical business practices. Furthermore, the paper delves into the concept of Marketing 5.0, which is defined by the incorporation of advanced technology into marketing strategies such as artificial intelligence (AI), the Internet of Things (IoT), and big data analytics. It emphasizes how consumer behavior is changing as a result of digitization and highlights new techniques used by businesses to interact with customers. Future trends discussed include the increased use of virtual and augmented reality, voice assistants, predictive analytics, automation, and AI-driven personalization, among others. A theoretical model is also proposed based on the qualitative analysis.
Keywords: M30; M31; 330; Marketing 5.0; Society 5.0; competitiveness; enterprises